Plasmid DNA Launches Live-Attenuated Japanese Encephalitis Virus and Elicits Virus-Neutralizing Antibodies in BALB/c Mice - Nickols, Brian (Virology, 2017)
We describe novel plasmid DNA that encodes the full-length Japanese encephalitis virus (JEV) genomic cDNA and launches live-attenuated JEV vaccine in vitro and in vivo. The synthetic cDNA based on the sequence of JEV SA14-14-2 live-attenuated virus was placed under transcriptional control of the cytomegalovirus major immediate-early promoter. The stability and yields of the plasmid in E. coli were optimized by inserting three synthetic introns that disrupted JEV cDNA in the structural and nonstructural genes. Transfection of Vero cells with the resulting plasmid resulted in the replication of JEV vaccine virus with intron sequences removed from viral RNA. Furthermore, a single-dose vaccination of BALB/c mice with 0.5 – 5 μg of plasmid resulted in successful seroconversion and elicitation of JEV virus-neutralizing serum antibodies. The results demonstrate the possibility of using DNA vaccination to launch live-attenuated JEV vaccine and support further development of DNA-launched live-attenuated vaccine for prevention of JEV infections.